1998
DOI: 10.1103/physrevlett.81.4903
|View full text |Cite
|
Sign up to set email alerts
|

First Principles Simulations of the Structure, Formation, and Migration Energies of Kinks on the 90° Partial Dislocation in Silicon

Abstract: The structure, formation, and migration energies of kinks on the 90 ± partial dislocation in silicon have been studied using a first principles method and periodic boundary conditions. Of the possible types of kinks only those that reverse the sense of the reconstruction of the dislocation on either side of them are found to be stable. Values of 0.04 6 0.03 and 1.09 6 0.03 eV for the formation and migration energies of these defects have been obtained and compared to experimental values. The structure and bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 26 publications
4
31
1
Order By: Relevance
“…The alternative mechanism invoking fully reconstructed kinks [31] has been found to have an activation energy of 1.8-1.9 eV [24,30], within Hirth-Lothe theory, in disagreement with 1.2 eV obtained by applying the same theory to other recent results [32]. Experimental measurements are in the region of 2.2 eV [2].…”
Section: Cor530contrasting
confidence: 37%
“…The alternative mechanism invoking fully reconstructed kinks [31] has been found to have an activation energy of 1.8-1.9 eV [24,30], within Hirth-Lothe theory, in disagreement with 1.2 eV obtained by applying the same theory to other recent results [32]. Experimental measurements are in the region of 2.2 eV [2].…”
Section: Cor530contrasting
confidence: 37%
“…More recently, using high-resolution electron microscopy, Kolar et al have determined that F k = 0.80 eV and W m = 1.24 eV for a 30 • partial dislocation [4]. Besides, many calculations have been performed, but the results are not conclusive enough because of the large scatter of computed energies [18][19][20][21]. For non-dissociated dislocations, to our knowledge, no experimental data are available for kinks.…”
mentioning
confidence: 99%
“…To the authors' knowledge, Nunes et al [13,14] studied the structures, the formation and migration energies of kinks in the 90° partial dislocation in silicon. In their work, it was found that the asymmetric core reconstruction generated at least four distinct kink species as well as soliton defects, and that there existed certain low-energy kinks.…”
mentioning
confidence: 99%